2007
DOI: 10.5465/amj.2007.25525647
|View full text |Cite
|
Sign up to set email alerts
|

Radical Change Accidentally: The Emergence and Amplification of Small Change

Abstract: A decision to offer breakfast to homeless people led to radical change in a church and its environment. Existing theories of change do not fully explain observations from our qualitative study; however, complexity theory constructs suggest how and why such change emerged. We offer four key findings. First, the radical change was unintended, emergent, and slow. Second, destabilizing conditions helped small changes to emerge and become radical. Third, subsequent actions amplified an initial small change and, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
333
1
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 419 publications
(356 citation statements)
references
References 54 publications
4
333
1
8
Order By: Relevance
“…First, McKelvey & Lichtenstein (in press) suggest that emergence occurs in increasingly complex stages and Plowman et al (2007) found some support for this idea. Learning more about the role of leadership at each stage of emergence will be important in furthering our understanding of leaders as enablers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, McKelvey & Lichtenstein (in press) suggest that emergence occurs in increasingly complex stages and Plowman et al (2007) found some support for this idea. Learning more about the role of leadership at each stage of emergence will be important in furthering our understanding of leaders as enablers.…”
Section: Discussionmentioning
confidence: 99%
“…1 This preamble study relied on an inductive approach, which is consistent with methodology used in similar research (Eisenhardt, 1989b;Isabella, 1990). Our initial review of decision-making processes ultimately became a study of continuous, radical change, which had started five years prior to our initial study (see Plowman et al, 2007). Findings from the study of radical change suggested that leadership was one of several factors contributing to the radical, and unintended organizational transformation at Mission Church.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations